Genome-Wide Identification of Histone Modifications Involved in Placental Development in Pigs - Han, Kun; Ren, Ruimin; Cao, Jianhua; Zhao, Shuhong; Yu, Mei (Frontiers in Genetics, 2019)
Development of placental folds is a critical event affecting placental function in pigs because it can increase surface area for improvement in capillary density as gestation advances. However, the molecular mechanisms of the event are not well defined. Histone modifications have important roles in gene regulation. To investigate their effects on regulation of genes controlling porcine placental development, RNA-seq and ChIP-seq of porcine placental tissues from gestational days 50 (establishment stage of placental folds) and 95 (expanding stage of placental folds) were carried out in this study. The differentially expressed genes were identified and of which the down- and up-regulated genes are related to endoplasmic reticulum (ER) stress and angiogenesis, respectively. In addition, we mapped the genome-wide profiles of histone H3 lysine 4 trimethylation (H3K4me3) and histone H3 lysine 27 acetylation (H3K27ac), which are associated with transcriptional activation. A number of differential modification regions between the 2 gestational stages were identified and majority of them are those with increased signals of H3K4me3 (14,576 out of 16,931). Furthermore, we observed that the increase of H3K4me3 is significantly correlated with the elevated expression levels of the neighboring genes, and notably, these genes were enriched in pathways related to blood vessel formation and microvascular permeability. Taken together, the findings suggest important roles of histone modifications on placental remolding in response to developmental changes.